Post neutron irradiation annealing and defect evolution in single crystal tungsten. (March 2023) - Papadakis, D.; Mergia, K.; Manios, E.; Chatzikos, V.; Dellis, S.; Messoloras, S.
Highlights: Neutron irradiated tungsten single crystal at 600 °C has been isochronally annealed from 700 to 1500 °C in steps of 100 °C. The total line density of dislocations, number density of voids and their size versus annealing temperature have been determined. From hardness, the critical resolved stresses arising from dislocations and voids have been derived and correlated with their densities. After annealing at 1500 °C the material, apart from clusters of Re, WRe and WOs2, is defect free and its hardness has been decreased to the pre-irradiation value. Abstract: Single crystal W is offered for Physics understanding of irradiation induced defects and their annealing as its structure is well defined and it is almost defect free. W(1 0 0) single crystal was neutron irradiated to a damage of 0.11 displacements per atom at 600 °C and subsequently isochronally annealed from 700 up to 1500 °C in 100 °C steps. Irradiation causes the formation of dislocation loops and vacancy clusters and a 45 % increase in hardness. After the annealing of 1500 °C the positron lifetime annihilation spectrum shows a defect free material and its hardness has been reverted to the pre-irradiation value and only clusters of Re, WRe and WOs2 have been detected by grazing incidence X-ray diffraction. The total line density of dislocations, number density of voids and their size versus annealing temperature have been determined. From hardness, the critical resolved stresses arising from dislocations and voids have been derived and correlated with their densities. The kinetics of defect annihilation versus annealing temperature is discussed.